PREVENTION OF ACADEMIC BURNOUT IN HIGH SCHOOL STUDENTS THROUGH GROUP GUIDANCE SERVICES WITH PRIORITY SCALE MAKING LIST TECHNIQUES - Yohana Fransisca; Abdul Aziz Rusman (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to examine the effectiveness of group counseling services using the priority scale listing technique in preventing academic burnout among students at SMA Negeri 1 Bilah Hulu. Academic burnout is a condition characterized by emotional exhaustion, decreased motivation to study, and feelings of helplessness, often experienced by students due to excessive academic pressure and ineffective time management. The research employed a quantitative approach with a pre-experimental design (one-group pretest-posttest design). The subjects of the study were 10 students identified as having moderate to high levels of academic burnout tendencies, based on initial assessments using a modified version of the Maslach Burnout Inventory–Student Survey (MBI-SS). The intervention consisted of five group counseling sessions incorporating the priority scale listing technique to help students organize their academic tasks and responsibilities more systematically. Data analysis using the Wilcoxon Signed Ranks Test revealed a significant reduction in academic burnout scores after the intervention (Z = -2.803, p < 0.005). These findings indicate that group counseling using the priority scale listing technique is effective in preventing and reducing symptoms of academic burnout among students. The implications of this study highlight the critical role of school counseling services in helping students develop effective time management and decision-making skills to better cope with academic demands.